1976
DOI: 10.1056/nejm197609092951103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Flora of Farm Personnel after Introduction of a Tetracycline-Supplemented Feed on a Farm

Abstract: A prospective study was undertaken to determine whether feeding farm animals antibiotics in feed caused changes in the intestinal bacterial flora of farm dwellers and their neighbors. Chickens were fed tetracycline-supplemented feed (tet-feed), and, as expected, within one week their intestinal flora contained almost entirely tetracycline-resistant organisms. Increased numbers of resistant intestinal bacteria also appeared, but more slowly, in farm members, but not their neighbors. Within five and six months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
149
0
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(157 citation statements)
references
References 22 publications
5
149
0
2
Order By: Relevance
“…We first analyzed some general trends such as the connection between use in animal husbandry and the spread of resistance, previously suggested from studies of one or a few antibiotics at a time (Levy et al 1976;Holmberg et al 1984;Hummel et al 1986;Bager et al 1997;Fey et al 2000). We observe a clear and significant increase in resistance gene abundance both for antibiotics approved for animal use by the U.S. FDA (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…We first analyzed some general trends such as the connection between use in animal husbandry and the spread of resistance, previously suggested from studies of one or a few antibiotics at a time (Levy et al 1976;Holmberg et al 1984;Hummel et al 1986;Bager et al 1997;Fey et al 2000). We observe a clear and significant increase in resistance gene abundance both for antibiotics approved for animal use by the U.S. FDA (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…As early as the 1970s Stuart Levy noted that oxytetracycline was a major feed additive and that studies had shown there was a strong association between tetracycline resistance in isolates from livestock and animal workers (Levy et al, 1976). The gene was detected in farmland soil previously amended with pig slurry containing resistant bacteria; the number of positive samples from farmland soils one year after manure treatment was significantly higher than in samples of garden soil not treated with manure.…”
Section: B Farm Animalsmentioning
confidence: 99%
“…It was reported that as much as 80% of total antibiotic production in the United States is used in agriculture, with a substantial portion of this used for the nontherapeutic purpose of growth promotion (4,5). AR bacteria have been found in farm animals where antibiotics are heavily used (6)(7)(8), in associated food products (9,10), in environments contaminated by animal waste (11,12), and in farm workers (13)(14)(15). Drugs that are used therapeutically in animals also may generate a reservoir of AR bacteria (16,17).…”
mentioning
confidence: 99%